“Having to Think in Inverted Commas”: Feminine Discourse and Foreign Words in Sarah Grand’s The Beth Book (1897) - Nathalie Saudo-Welby (Revue LISA)
The Beth Book is a feminist novel belonging to the genre of New Woman fiction, telling the Bildung of a woman of genius. Beth owes her talent for public speaking to her childhood days in Victorian Ireland, where she was sensitized to oral storytelling and to the politics of language. Beth feels estranged from her mother tongue, the language of the patriarchal canon, the hypercorrect English which is taught to young ladies. Beth “only ha[s] one language, yet it is not [hers]” (Derrida). Her apprenticeship will take her through the traditional phases of imitation and purge, but her conquest of language is presented as a return to a magical language of origins, which speaks through her rather than is spoken by her. Is female genius meant to preserve rather than create? Once she becomes an orator, her speeches make people raise their fists and cause inverted commas to fall.